Biopotential changes of acupuncture points by acupuncture stimulation - Seong Jin Cho; Kwang-Ho Choi; Min Ji Kim; O Sang Kwon; Suk Yun Kang; Su Yeon Seo; Yeonhee Ryu (Integrative Medicine Research)
Background: The energy flow at acupuncture point is important for understanding the mechanism of acupuncture treatment. However, there are few studies on energy at acupuncture point, and related studies have limitation in explaining the energy flow in all meridians. Thus, we aimed to understand the properties of electrical energy at acupuncture point in twelve meridians by measuring the biopotential at acupuncture and non-acupuncture points. Methods: For each meridian, twenty subjects were participated, and biopotential was measured at five transport points and their adjacent non-acupuncture points. In each subject, both ‘non-stimulation’ and ‘stimulation’ experiments were conducted in random order. The data were analyzed in two parts: biopotential variability and biopotential difference between acupuncture and non-acupuncture points. Results: The biopotential variability at acupuncture point was increased by acupuncture stimulation, and it was related to the activation of Qi flow by acupuncture stimulation. The biopotential difference between acupuncture and non-acupuncture points was formed in the direction related to the Qi flow theory, and this biopotential difference tended to decrease by acupuncture stimulation. Conclusion: The study on biopotential can provide a foundation for research on energy flow mechanism of acupuncture stimulation, and it is expected to overcome limitation of qualitative explanation in traditional medicine.